FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN KARIES GIGI - Veronica Anggreni Damanik (Politeknik Kesehatan Kemenkes Sorong, 2020)
ABSTRACTBackground Dental caries is a chronic disease in the form of continuous and loss of mineral ions from theenamel surface on root surface of a tooth. According to (WHO) 2016 the incidence of child caries is still 60-90%. Theresults of research in European countries, America and Asia including Indonesia, it turns out that 90-100% of childrenunder 18 years old affected by dental caries. North Sumatra Province in elementary school, students who have donemass toothbrushes is amount 1,490 or 17.19% of the total number of primary schools amount 8,869. This study aims todetermine the factors related to the incidence of dental caries in Students of SDN 105273 Helvetia Medan in 2019. Thedesign of this research is analytical survey. The population was 66 people and all were sampled by total populationtechnique. Data collection methods were primary, secondary and tertiary data and analyzed by Chi-square test. Theresults showed the perception with a level of confidence α = .05, the habit of brushing teeth obtained p-value = .006<from α = 0.05, cariogenic food obtained p-value = .003 <from α = .05, knowledge obtained p-value = .027 <of α =.05. Thus it showed there was the relationship between factors related to the incidence of dental caries in the School.The conclusion shows that there was the relationship between the habit of brushing teeth, cariogenic food, andknowledge with the incidence of dental caries in students of SDN 105273 Helvetia Medan in 2019. It is recommendedthat students be able to maintain their dietary habit and habit of brushing their teeth in order to maintain dentalhealth.Keywords: Tooth Brushing Habits, Cariogenic Food, Knowledge, Dental CariesABSTRAKPendahuluan: Karies gigi adalah penyakit kronis prosesnya berlangsung cukup lama, berupa hilangnya ion-ionmineral secara kronis dan terus-menerus dari permukaan email pada mahkota atau permukaan akar gigi. Menurut(WHO) 2016 kejadian karies anak masih sebesar 60-90%. Hasil penelitian di negara-negara Eropa, Amerika dan Asiatermasuk Indonesia, ternyata 90-100% anak di bawah 18 tahun terserang karies gigi. Provinsi Sumatera Utara padasiswa SD yang pernah melakukan sikat gigi masal sebanyak 1.490 SD atau sebesar 17,19% dari total jumlah SDsebanyak 8.869 SD. Tujuan dalam penelitian ini mengetahui Faktor-Faktor yang Berhubungan dengan Kejadian KariesGigi pada Siswa SDN 105273 Helvetia Medan. Desain penelitian ini adalah survey analitik. Populasi penelitian inisebanyak 66 orang dan pengambilan sampel penelitian ini menggunakan tehnik Total Sampling yaitu tehnikpengambilan sampel dimana jumlah hasil dari populasi ditetapkan menjadi sampel yang berjumlah 66 orang. Metodepengumpulan data yaitu data primer, sekunder dan tertier. Analisi data yang digunakan dengan uji Chi-square. Hasilpenelitian menunjukkan presepsi dengan tingkat kepercayaan α = 0,05, kebiasaan menggosok gigi diperoleh nilai p=0,006 <dari α = 0,05, makanan kariogenik diperoleh nilai p= 0,003<dari α = 0,05, pengetahuan diperoleh nilai p= 0,027<dari α = 0,05. Kesimpulan penelitian ini ada hubungan kebiasaan menggosok gigi, makanan kariogenik, danpengetahuan dengan kejadian karies gigi di SDN 105273 Helvetia Medan. Disarankan para siswa dapat menjaga polamakan dan kebiasaan menggosok gigi guna menjaga kesehatan gigi.Kata Kunci : Kebiasaan Menggosok Gigi, Makanan Kariogenik, Pengetahuan, Karies Gigi